Mathematics of medical science – solution or problem? - Shrestha, Ashis (Journal of General Practice and Emergency Medicine of Nepal, 2015)
Research and evidences have very important roles in clinical practices. Modern day practices are based on evidence based medicines. With this, medical science is getting more quantitative and specific. Disease is no more just signs and symptoms; it is now measurable in rates and ratios. Investigations are no more just a laboratory test; it has measurable sensitivity and specificity. We can now estimate mortality of morbid conditions in percentage and add up our confidence with “P value”. We have changed disease into mathematics, medicine into statistics and living into probability. “An essence of time.”